Sex-linked, androgen-dependent differences in renal retention of trimethylselenonium ions - Parízek, J; Kalousková, J; Pavlík, L; Stýblo, M (Biological trace element research, 1992)
The metabolism of trimethylselenonium ions (TMSe) was studied in male and female rats during maturation. Selenium (Se) retention in the whole body as well as in organs was found to be significantly higher in male rats than in female a few hours after parenteral administration of TMSe. The pronounced Se accumulation was observed in male kidneys. This sex-linked difference was dependent on the presence of gonads and started to be manifested with sexual maturation during the third decade of postnatal life. The effects of steroid hormones on the retention of Se from TMSe were examined in female and castrated male rats. The results indicate that TMSe metabolism in rat kidneys may be influenced by androgen steroids.
Keywords: selen; Sexual Maturation; Selenium Compounds; ledviny; Female; Kidney; krysa rodu Rattus; zvířata; Selenium; potkani Wistar; sloučeniny selenu; ženské pohlaví; Rats, Wistar; Male; Testosterone; Sex Characteristics; pohlavní dimorfismus; pohlavní dospělost; Rats; Animals; mužské pohlaví; testosteron